MHD Peristaltic Transport of a Dusty Couple Stress Fluid Through a Symmetric Porous Channel - P. Siva, E.; Prakash, `J.; Govindarajan, A.; Vidhya, M. (International Journal of Engineering and Technology, 2018)
This paper agreement with the MHD peristalsis flow of a dusty couple stress liquid in a 2-D channel. Analytical solutions are got for pressure gradient and axial velocity in the fluid using perturbation technique. The results obtained for velocity profile, pressure gradient and skin friction are graphically represented. It is noted the velocity profiles increases with the increase in time averaged flow rate (Q). The velocity profiles reduce with the raise in couple stress parameter (S) and Permeability parameter (k).Â